2002
DOI: 10.1034/j.1600-0587.2002.250401.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable responses of waterfowl breeding populations to long‐term removal of introduced American mink

Abstract: It is suspected that feral American mink, an introduced predator in Europe, have seriously affected local densities of birds breeding in archipelagos and coastal areas. We studied the effects of mink removal on breeding densities of waterfowl in two manipulation and two control areas in the outer archipelago of SW Finland, Baltic Sea. The study was conducted in two phases: during 1992–2001 a total of 98 mink was removed from 60 islands and islets (total area 72 km2) whereas on 37 islands and islets (35 km2) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 37 publications
(42 reference statements)
3
64
3
Order By: Relevance
“…These include velvet scoter (Melanitta fusca), red-breasted merganser (Mergus serrator), and black guillemot (Andersson 1999). Recent mink control experiments in Baltic Finnish islands have shown how mink removal benefits a wide range of ground-nesting (mainly aquatic) birds, especially smaller species (Nordstrom et al 2002(Nordstrom et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…These include velvet scoter (Melanitta fusca), red-breasted merganser (Mergus serrator), and black guillemot (Andersson 1999). Recent mink control experiments in Baltic Finnish islands have shown how mink removal benefits a wide range of ground-nesting (mainly aquatic) birds, especially smaller species (Nordstrom et al 2002(Nordstrom et al , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, partially as a consequence of habitat loss, the global waterbird population has decreased by 44 % in the few past years alone (Delany et al 2010) and numerous studies have reported notable declines in waterbirds on a local scale (Crowe et al 2008;Ma et al 2009;Sandilyan et al 2010). However, very little is known about the part played by invasive species in this decline, with the exception of the well-documented role of predatory alien mammals such as, for instance, the American mink Neovison vison (Nordström et al 2002;Brzeziński et al 2012) or the raccoon Procyon lotor (Ellis et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Black adders (Vipera berus) are widespread in Scandinavian archipelagos (Forsman and Lindell 1997) and are regularly observed during summer on all study islands, though not during the autumn trapping before, and the spring trapping after, food supplementation which was carried out on cold days. Additionally, short-and longeared owls (Asio flammeus and A. otus) and Eurasian kestrels (Falco tinnunculus) may exert some predation pressure on voles during spring and autumn migration Nordström et al 2002).…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…In the archipelagos of the Baltic Sea, mink have been shown to exert strong predation pressure on voles, sea-birds and amphibians, thus having vast detrimental effects on the biodiversity (Ahola et al 2006;Banks et al 2004Banks et al , 2008Nordström et al 2002;Nordström and Korpimäki 2004). The American mink is a North American mustelid which has continually escaped from Fennoscandian fur farms for more than 60 years and is now widespread throughout semi-aquatic ecosystems in Finland (Kauhala 1996;Niemimaa 1995).…”
Section: Introductionmentioning
confidence: 97%